Pemanfaatan Tithonia Diversifolia pada Tanah Sawah yang Dipupuk P Secara Starter terhadap Produksi serta Serapan Hara N, P, dan K Tanaman Padi - . Gusnidar; Teguh Budi Prasetyo (UNIVERSITY OF LAMPUNG, 2008)
The research of Tithonia diversifolia utilization in the paddy soil that was fertilized P-starter on yield and N, P, K uptake on rice crop, has been conducted from August to December 2005. The objective of this research was to determine interaction between P-starter levels, and tithonia levels on production and N, P, K element uptake of rice crop. The research was pot experiment in the green house in factorial design 4 x 4. First factor was 4 levels of tithonia with reduce dosage fertilizer aplied (T0 = 0 t tithonia + 200 kgUrea ha-1 + 75 kg KCl ha-1; T1= 2,5 t tithonia ha-1 + 150 kg Urea ha-1, without KCl; T2 = 5,0 t tithonia ha-1 + 100 kg Urea ha-1, without KCl; dan T3 = 7,5 t tithonia ha-1 + 50 kg Urea ha-1, without KCl). The second factor was 4 levels of P-starter (0, 2, 4, and 6 kg P ha-1). The result showed that combination T3 treatment and 2-4 kg P-starter ha-1 increased the grain yield 20,51-21,08 g pot-1 (18,65-19,21%). Effect of T3 treatment was not significant with T2 treatment on the grain yield. The best interaction was T3 treatment on N and K uptake ((0,84 g pot-1 for N, dan 0,82 g pot-1 for K).